Penerapan WFH Sebagai Implikasi Transformasi Strategi Bursa Efek Indonesia Kantor Perwakilan Jambi Dalam Meningkatkan Literasi Pasar Modal - Sarah Sinadela; Netty Herawaty; Muhammad Ridwan (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This research aims to describe the transformation of the Jambi Representative Indonesia Stock Exchange (BEI) strategy in increasing capital market literacy during the Covid-19 pandemic after the implementation of Work From Home (WFH), education, socialization and various activities carried out as well as challenges and Problem Solving. This study uses a descriptive qualitative approach, with data collection techniques literature study, interviews, and documentation. Interviews were conducted with the Head of the Indonesia Stock Exchange Jambi Representative Office, Trainers, and Administrative Staff. The data analysis technique is done by inductive thinking. The results of the research show that there are strategies carried out by the Indonesia Stock Exchange (IDX) Jambi Representative Office, namely socialization and education strategies and other strategies in the form of digitalization strategies. Activities from this socialization and education strategy include public outreach, capital market schools (SPM), Islamic capital market schools (SPMS), visiting several agencies, establishing Investment Galleries, collaborating with securities companies and digitalization strategies, namely social media as a medium for disseminating information capital market. Challenges and problem solving include lack of understanding of digital applications and skills, limited internet and network access, lack of understanding of digital media communication culture.Â